Identifikasi Kegagalan Pada Stasiun Klarifikasi Menggunakan Metode Failure Mode And Effect Analysis Di PT. Surya Panen Subur 2 - Rizka Hartati Telaumbanua; Sofiyanurriyanti Sofiyanurriyanti (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
At the palm oil mill there is a purification station, namely the clarification station. The function of the purification station is as a separator of oil and impurities and to be able to obtain CPO in a completely pure state. At the crude palm oil refining station, it is processed and purified, namely the extracted oil from the press machine. standard oil is obtained. There are a number of machines that are ready to work for a long time during the processing at the refining station, so as a result, if there is damage to the machine, the processing will fail. In order for the purification station to operate smoothly, maintenance activities are activities that need to be carried out, especially in critical areas. It can be identified using the FMEA to select the most appropriate maintenance activities for critical parts. Therefore, the purpose of this study was to determine the critical parts of the purification station using the FMEA method. The procedure for finding the results of observations are (1) Collecting materials in the form of data, (2) Identifying critical parts, (3) Selecting maintenance activities. The results of this observation are that the critical parts at the purification station are found in the auto valve and valve inlet with an RPN value of 432. Thus, maintenance activities are carried out by replacing components (replacement).